2016
DOI: 10.1002/eji.201546266
|View full text |Cite
|
Sign up to set email alerts
|

Increased numbers of CD23+CD21hi Bin‐like B cells in human reactive and rheumatoid arthritis lymph nodes

Abstract: A unique population of CD23+ CD21high B cells in inflamed nodes (Bin) has been shown to accumulate in lymph nodes (LNs) draining inflamed joints of TNF-transgenic (TNF-tg) mice. Bin cells contribute to arthritis flare in mice by distorting node architecture and hampering lymphatic flow, but their existence in human inflamed LNs has not yet been described. Here, we report the characterization of resident B-cell populations in fresh popliteal lymph nodes (PLNs) from patients with severe lower limb diseases (non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 17 publications
4
26
0
Order By: Relevance
“…Recent investigations suggest a contribution from circulating IgD + immature B lymphocytes and PRIME cells, as well as synovial macrophage populations (8,9). These novel observations are also consistent with our model of lymphatic dysfunction in RA flare 7, as: 1) the circulating IgD + B-cells may be the Bin cells that we observe within the lymphatic sinuses (20,21,35), 2) the circulating PDPN + PRIME cells may be lymphatic endothelial progenitors that are mobilized to repair damaged lymphatic vessels, and 3) the activated adherent macrophages in the lumen of degenerated PLVs (42) are likely from the afferent inflamed synovium (35,43).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recent investigations suggest a contribution from circulating IgD + immature B lymphocytes and PRIME cells, as well as synovial macrophage populations (8,9). These novel observations are also consistent with our model of lymphatic dysfunction in RA flare 7, as: 1) the circulating IgD + B-cells may be the Bin cells that we observe within the lymphatic sinuses (20,21,35), 2) the circulating PDPN + PRIME cells may be lymphatic endothelial progenitors that are mobilized to repair damaged lymphatic vessels, and 3) the activated adherent macrophages in the lumen of degenerated PLVs (42) are likely from the afferent inflamed synovium (35,43).…”
Section: Discussionsupporting
confidence: 89%
“…These longitudinal imaging studies combining contrast enhanced (CE) MRI of the synovium and popliteal lymph node (PLN) (12), with quantification of lymphatic drainage via near infrared (NIR) imaging of an injected dye (indocyanine green, ICG) (15), demonstrated that prior to detectable synovial hyperplasia in the knee, the adjacent PLN expands. This PLN expansion is associated with increased lymphangiogenesis, elevated volume, CD11b + macrophage infiltration, and the accumulation of a unique subset of IgD + /CD23 + /CD21 hi B cells in inflamed nodes (B-in) (15)(16)(17)(18)(19)(20)(21). This asymptomatic "expansion" phase is followed by a sudden "collapse" of the PLN, which is objectively defined by quantitative CE-MRI or power Doppler ultrasound (PD-US) imaging of the PLN (12,22).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we demonstrated that progression of arthritis in the knee joints of TNF-transgenic mice is paralleled by dramatic changes in the draining lymph nodes (LNs) (6)(7)(8). Those longitudinal imaging studies combining contrast-enhanced magnetic resonance imaging (CE-MRI) of the synovium and popliteal LNs (6) with quantitation of lymphatic drainage via near-infrared (NIR) imaging of an injected dye (indocyanine green [ICG]) (9) demonstrated that prior to detectable synovial hyperplasia in the knee, the adjacent popliteal LN expands due to increased lymphangiogenesis, lymphatic fluid accumulation, CD11b1 macrophage infiltration, and the expansion of a unique subset of CD231/CD21 high B cells in inflamed nodes (5,(9)(10)(11)(12)(13)(14). This asymptomatic "expansion" phase is followed by a sudden "collapse" of the popliteal LN, which is identified by CE-MRI or power Doppler imaging of the popliteal LN (6,15).…”
mentioning
confidence: 99%
“…This phenomenon is related to translocation of specific B-cell subsets (Bin, B cells in inflamed nodes) in the paracortical sinuses, and is coupled to decreased PD signal and defective lymphatic flow [ 47 , 48 ]. Of relevance, LN Bin, whose presence in humans has been proved recently [ 49 ], can be removed by systemic B-cell depletion [ 47 ], but are marginally affected by anti-TNF [ 50 ]. Introduction of treatment in a phase in which a central lymphatic road-block is active might thus limit some of the beneficial effects of anti-TNF that include peripheral lymphangiogenesis [ 51 ] and increased lymphatic contraction [ 50 ].…”
Section: Discussionmentioning
confidence: 99%